Study of the allelopathic effect of aqueous extracts (leaves - tubers) of the Arum palaestinum Boiss. on seed germination and seedling growth of Malva sylvestris L. and .Portulaca oleracea L.: دراسة التأثير الأليلوباثي للمستخلصات المائية (أوراق - درنات ) لنبات اللوف الفلسطيني(.Boiss (Arum palaestinum في إنبات ونمو بادرات الخبيزة Malva sylvestris L.)) والبقلة Portulacca oleracia L.)). (Latakia University Journal -Biological Sciences Series, 2025)
The allelopathic effect of the the Arum palaestinum Boiss. on the germination and growth of Malva sylvestris L. and .Portulaca oleracea L. aqueous extracts of leaves and tubers were obtained separately at different concentrations (2, 4, 6, 8%) in addition to the control. The average length of the stalk and root decreased with increasing concentration of the filtrate he differences were significant for the difference of the mean with the control at the 0.05 level, and the concentration of 2% took the highest value for the relative germination rate and average root length The percentage of inhibition and the relative length of the stem in the test plants. The inhibition rates for the stem, root, and germination rate were greater than one for all treatments, so they had a negative inhibitory effect. The 8% treatment for leaves and tubers had the highest rate of inhibition on the test plants together. The results also showed that the leaves had a greater allelopathic inhibitory effect Compare with tubers.